The Relationship of Dietary Pattern and Sarcopenia in Type II Diabetes Mellitus Patients - Kedang, Veronika Merika; Syauqy, Ahmad; Margawati, Ani (JURNAL INFO KESEHATAN, 2024)
Diet plays an important role in managing mass, and muscle strength and preventing diseases related to malnutrition. A dietary pattern that contains several nutrients has a role in improving muscle performance and reducing the incidence of sarcopenia. This study aims to determine the relationship between dietary patterns and the incidence of sarcopenia in subjects with type 2 diabetes mellitus. This study was a cross-sectional study conducted on 150 subjects with type 2 diabetes mellitus aged 40 years or older. Multivariate logistic regression tests were conducted to measure the effect of adherence to each dietary pattern on the possibility of sarcopenia. Three dietary patterns were identified through analysis of major components. After adjusting for confounding variables, subjects with healthy dietary patterns on the highest tertile had a lower odds ratio for developing sarcopenia (OR 0.584; 95% CI 0.070-4.865; p=0.000). In contrast, adherence to unhealthy dietary patterns was not associated with sarcopenia (OR 1.508; 95% CI 0.305-7.452; p=0.612).  Similarly, adherence to a mixed dietary pattern did not affect the likelihood of sarcopenia (OR 1.297; 95% Cl 0.341-4.931; P=0.704). This study shows that adherence to a healthy dietary pattern is associated with a lower chance of developing sarcopenia in people with type II diabetes mellitus.